Some More Solitary Traveling Wave Solutions of Nonlinear Evolution Equations - Behera, S.; Virdi, J. P. S. (Discontinuity, Nonlinearity, and Complexity, 2026)
In present work, we apply a novel (G’G)-formalism to construct more general solitary traveling wave solutions of Nonlinear Evolution Equations (NLEEs) such as Vakhnenko equation (VE), Camassa-Holm equation (CH), Symmetric Regularized Longwave Equation (SRWE). Method that we have chosen, is simple, straightforward and, gives the three types of solutions including trigonometric, exponential, and rational solutions as compared to other existing methods. Distinct periodic and solitary wave solutions are derived witch are rich in structure and gives wide range of solution under different parametric regime. Wolfram Mathematica 11 is used to perform the computation work and their corresponding plots and counter graphs are plotted using Matlab.